Dinamika Koneksi Politik dan Keberagaman Gender TMT dalam Memengaruhi Transparansi Pelaporan Keuangan - Talita Adelia Zahira; Mukhtaruddin Mukhtaruddin (CV. ITTC INDONESIA, 2026)
Financial reporting transparency is a crucial element for economic decision-making, yet its integrity is often influenced by internal governance structures and the external political environment. This study aims to examine and summarize scientific findings regarding the influence of gender diversity in Top Management Teams (TMT) and political connections on financial reporting transparency. Using the Systematic Literature Review (SLR) method, this research analyzes 18 scientific articles published between 2020 and 2026. The review results indicate that gender diversity consistently has a positive impact on the quality of corporate information through improved accrual quality, disclosure of Environmental, Social, and Governance (ESG) performance, and the prevention of fraudulent activities. Conversely, political connections act as a